PENINGKATAN KEMAMPUAN MENULIS TEKS BUKU HARIAN DENGAN MENGGUNAKAN MODEL BELAJAR KOOPERATIF TIPE STAD PADA SISWA KELAS II SD NEGERI 18 AIR TAWAR SELATAN - Najmi Hayati; Zuraida Khairani; Dwi Mutia Chan (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
This research is motivated by the fact in the field that the writing ability of students in grade II SD Negeri 18 Air Tawar Selatan is still low. This condition results in low student learning outcomes in Indonesian subjects under the KKM that has been set, namely 70. This study aims to improve writing skills using the STAD Type Cooperative learning model for class II State Elementary School 18 Air Tawar Selatan. This type of research is Classroom Action Research (CAR), where the teacher is the implementer of learning while the researcher is the observer. The design of this study uses the Kemmis and Mc. This research was conducted in the even semester of the 2018/2019 academic year, namely in September. The subjects of this study were second grade students of SDN 18 Air Tawar Selatan, which consisted of 30 students. The object of research is student learning activity. Data collection techniques using observation and interviews. Data were analyzed descriptively and presented in the form of tables and graphs. Based on the improvement of learning that has been carried out from Pre-Cycle learning, Cycle I and Cycle II, it is seen that there is an increase in student learning outcomes, namely from the Pre-Cycle Average score of 58.7,3 with a percentage of completeness 29.41% while in the first cycle the average value an average of 70.29 with the percentage of completeness increased to 70.5%, and increased again in the second cycle to 100% with an average value of 80.29. The use of the STAD Type Cooperative learning model in learning Indonesian in class II SD Negeri 18 Air Tawar Selatan can improve student learning outcomes.